Synthesis, characterization and effect of sintering temperature on magnetic properties of MgNi ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Chavan, Santosh S.; Waghmare, K. J.; Chougule, B. K. (Journal of Alloys and Compounds, 2009)
Mixed MgNi ferrites with composition Mg(0.5)Ni(0.5)Fe(2)O(4) where the mole fraction for Ni (x = 0, 0.25, 0.75, 0.5 and 1) were prepared by following co-precipitation method at temperature 110 degrees C and maintaining a pH of solution equal to 9.5 enable to achieve large particle surface area. The resultant materials obtained in powder form were sintered at different temperatures. Thermogravimetry (TGA), X-ray diffraction (XRD) and scanning electron microscopy, technique were applied to obtain structural parameters. The XRD patterns reveal the presence of(311) peak as the most intense one. The intensity of XRD peak increases with increase in sintering temperature. The saturation magnetization values showed increasing trend with increase in sintering temperature from 2.37 to 29.76 emu/g. These results along with the analysis of SEM micrographs are interpreted in terms of increase in particle grain size with increase in sintering temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Ferrites; FT-IR; scanning electron microscopy; X-ray diffraction